Exposure of the stingless bee Melipona scutellaris to imidacloprid, pyraclostrobin, and glyphosate, alone and in combination, impair its walking activity and fat body morphology and physiology - Farder-Gomes, Cliver Fernandes; de Oliveira, Marco Antônio; Malaspina, Osmar [UNESP]; Nocelli, Roberta Ferreira Cornélio (My University, 2024)
The stingless bee Melipona scutellaris performs buzz pollination, effectively pollinating several wild plants and crops with economic relevance. However, most research has focused on honeybees, leaving a significant gap in studies concerning native species, particularly regarding the impacts of pesticide combinations on these pollinators. Thus, this study aimed to evaluate the sublethal effects of imidacloprid (IMD), pyraclostrobin (PYR), and glyphosate (GLY) on the behavior and fat body cell morphology and physiology of M. scutellaris. Foragers were orally exposed to the different pesticides alone and in combination for 48 h. Bees fed with contaminated solution walked less, moved slower, presented morphological changes in the fat body, including vacuolization, altered cell shape and nuclei morphology, and exhibited a higher count of altered oenocytes and trophocytes. In all exposed groups, alone and in combination, the number of cells expressing caspase-3 increased, but the TLR4 number of cells expressing decreased compared to the control groups. The intensity of HSP70 immunolabeling increased compared to the control groups. However, the intensity of the immunolabeling of HSP90 decreased in the IMD, GLY, and I + G (IMD + GLY) groups but increased in I + P-exposed bees (IMD + PYR). Alternatively, exposure to PYR and P + G (PYR + GLY) did not affect the immunolabeling intensity. Our findings demonstrate the hazardous effects and environmental consequences of isolated and combined pesticides on a vital neotropical pollinator. Understanding how pesticides impact the fat body can provide crucial insights into the overall health and survival of native bee populations, which can help develop more environmentally friendly approaches to agricultural practices.
Keywords: Cell death; Immune defense; Pollination; Sublethal effects; Toxicology